European Maxillofacial Trauma (EURMAT) project: A multicentre and prospective study. Issue 1 (January 2015) - Boffano, Paolo; Roccia, Fabio; Zavattero, Emanuele; Dediol, Emil; Uglešić, Vedran; Kovačič, Žiga; Vesnaver, Aleš; Konstantinović, Vitomir S.; Petrović, Milan; Stephens, Jonny; Kanzaria, Amar; Bhatti, Nabeel; et al.
Abstract The purpose of this study was to analyse the demographics, causes and characteristics of maxillofacial fractures managed at several European departments of oral and maxillofacial surgery over one year. The following data were recorded: gender, age, aetiology, site of facial fractures, facial injury severity score, timing of intervention, length of hospital stay. Data for a total of 3396 patients (2655 males and 741 females) with 4155 fractures were recorded. The mean age differed from country to country, ranging between 29.9 and 43.9 years. Overall, the most frequent cause of injury was assault, which accounted for the injuries of 1309 patients; assaults and falls alternated as the most important aetiological factor in the various centres. The most frequently observed fracture involved the mandible with 1743 fractures, followed by orbital-zygomatic-maxillary (OZM) fractures. Condylar fractures were the most commonly observed mandibular fracture. The results of the EURMAT collaboration confirm the changing trend in maxillofacial trauma epidemiology in Europe, with trauma cases caused by assaults and falls now outnumbering those due to road traffic accidents. The progressive ageing of the European population, in addition to strict road and work legislation may have been responsible for this change. Men are still the most frequent victims of maxillofacial injuries.